Proceedings of Corfu Summer Institute 2019 "School and Workshops on Elementary Particle Physics and Gravity" — PoS(CORFU2019) 2020
DOI: 10.22323/1.376.0226
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Snyder model

Abstract: We review the main features of the relativistic Snyder model and its generalizations. We discuss the quantum field theory on this background using the standard formalism of noncommutaive QFT and discuss the possibility of obtaining a finite theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In the Snyder model (β > 0), space is discrete and time is continuous, whereas in the anti-Snyder model (β < 0), time is discrete and space is continuous. The sub-algebra involving J µν and x µ is isomorphic to the de Sitter/anti-de Sitter algebra, thereby linking the momentum spaces of Snyder/anti-Snyder models geometrically to de Sitter/anti-de Sitter spacetimes [45]. Refining the Snyder model with isotropic parametrizations while maintaining Lorentz/Poincaré symmetry, lead to the same non-commutative relation and different forms of GUP as elaborated in [46,47].…”
Section: Quantum Spacetime: a Necessitymentioning
confidence: 98%
“…In the Snyder model (β > 0), space is discrete and time is continuous, whereas in the anti-Snyder model (β < 0), time is discrete and space is continuous. The sub-algebra involving J µν and x µ is isomorphic to the de Sitter/anti-de Sitter algebra, thereby linking the momentum spaces of Snyder/anti-Snyder models geometrically to de Sitter/anti-de Sitter spacetimes [45]. Refining the Snyder model with isotropic parametrizations while maintaining Lorentz/Poincaré symmetry, lead to the same non-commutative relation and different forms of GUP as elaborated in [46,47].…”
Section: Quantum Spacetime: a Necessitymentioning
confidence: 98%
“…Because this is a quantum-mechanical setting, we will work in the nonrelativistic limit of the Snyder model. 2 Until recently, this limit was usually taken by simply considering the three-dimensional Euclidean version of the model, thus neglecting the role of the time coordinate [27,28,29,30,31]. However, in [5] it was shown that taking explicitly the limit for c → ∞ gives rise to more complicated relations, where a mixing between time and space variables is still present.…”
Section: Introductionmentioning
confidence: 99%